Seeing is believing: Visualization of He distribution in zircon and implications for thermal history reconstruction on single crystals - Danišík, Martin; McInnes, Brent; Kirkland, Chris; McDonald, Brad; Evans, Noreen; Becker, Thomas (2017)
Zircon (U-Th)/He thermochronometry is an established radiometric dating technique used to place temporal constraints on a range of thermally sensitive geological events, such as crustal exhumation, volcanism, meteorite impact, and ore genesis. Isotopic, crystallographic, and/or mineralogical heterogeneities within analyzed grains can result in dispersed or anomalous (U-Th)/He ages. Understanding the effect of these grain-scale phenomena on the distribution of He in analyzed minerals should lead to improvements in data interpretation. We combine laser ablation microsampling and noble gas and trace element mass spectrometry to provide the first two-dimensional, grain-scale zircon He "maps" and quantify intragrain He distribution. These maps illustrate the complexity of intracrystalline He distribution in natural zircon and, combined with a correlated quantification of parent nuclide (U and Th) distribution, provide an opportunity to assess a number of crystal chemistry processes that can generate anomalous zircon (U-Th)/He ages. The technique provides new insights into fluid inclusions as potential traps of radiogenic He and confirms the effect of heterogeneity in parent-daughter isotope abundances and metamictization on (U-Th)/He systematics. Finally, we present a new inversion method where the He, U, and Th mapping data can be used to constrain the high- and low-temperature history of a single zircon crystal.